The use of enhanced nozzle maps for gas-turbine performance modelling - Al-Akam, Aws A.; Nikolaidis, Theoklis; MacManus, David G.; Pellegrini, Alvise (American Society of Mechanical Engineers (ASME), 2021)
The use of a simulation tool to predict the aero-engine performance before committing to a final engine design has become one of the most cost-saving approaches in this field. However, most of these tools are based on low fidelity thermodynamic models, which are incapable of fully capturing the impact of three-dimensional flow characteristics. An aero-engine exhaust-system is one of the essential components that affect the engine performance. Currently, engine performance models tend to utilize simplified nozzle performance maps. These maps typically provide information over a very limited range of nozzle geometries, which may not apply to the wide range of architectures and designs of aeroengines. The current paper presents a methodology for the development of nozzle performance maps, which takes into account the aerodynamic and the geometric parameters of the nozzle design. The methodology is based on the reduced-order models. These models are integrated into a zero-dimensional engine performance code to improve the accuracy of its thrust calculation. The impact of the new thrust model on the overall engine performance and the operating point is analysed and discussed. The results showed that the implementation of the modified maps, which take into account the flow characteristics and the geometry of the nozzle, affects the thrust calculation. In a typical case of a turbofan operating at cruise conditions, the net thrust estimation with the modified nozzle maps showed a difference of 0.2%, compared with the simple nozzle maps. The new thrust calculation method has the advantage in capturing the multidimensional impact of the flow of the nozzle as compared with the conventional one. Furthermore, the implementation of the new method reduces the uncertainties introduced by a simplified nozzle model and, consequently, it can support the decision-making process in the design of the engine.
Keywords: engine performance; aero-engine; nozzle modelling; nozzle maps